The Clinical Usefulness of the Practice Resource for Driving after Stroke (PReDAS). Issue 1 (3rd January 2023) - Vander Veen, April; Cammarata, Michael; Renner, Sarah; Alvarez, Liliana
Abstract: Occupational Therapists (OTs) have identified a critical need for organized, evidence-based resources to approach driving post-stroke. The Practice Resource for Driving After Stroke (PReDAS) is a resource to support the clinical reasoning and practice of health professionals for addressing driving in acute stroke care. The purpose of this pilot study is to evaluate the usefulness of the PReDAS to support clinician and patient decision-making about return to driving after stroke/Transient Ischemic Attack (TIA) in the acute care hospital setting. OTs, physicians, and patients diagnosed with stroke/TIA were surveyed regarding their experience with the PReDAS in acute care. Patient participants were also contacted for a follow-up questionnaire. OT, physician and patient stakeholders reported the PReDAS was useful to support decision-making for driving. The majority of patients recalled information provided in acute care and abstained from driving as advised. This study provides preliminary support for the clinical usefulness of the PReDAS.